2020
DOI: 10.3389/fvets.2020.00338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma reesei Degraded Date Pits on Antioxidant Enzyme Activities and Biochemical Responses of Broiler Chickens

Abstract: The long-term use of antimicrobials as growth promoters in poultry feed leads to antimicrobial resistance in pathogens. Thus, alternatives to antibiotics are essential for reasons associated with both safety and cost-effectiveness. Underutilized plant sources need to be developed to replace antibiotics in broiler feed. Several feed resources have been introduced so far, but they have yet to be applied widely. Date pits are a major by-product of the date industry (6-8%) and have the potential antioxidant to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Further, the supplementation with 0.2% mannanoligosaccharides (MOS) in a broiler significantly increased the weight of the duodenum, jejunum, and ileum at 42 days, while the group that was administered with oxytetracycline showed a decrease in weight in the jejunum. In the same study, the length of the duodenum increased significantly in chickens fed MOS, and a decrease in length was shown for the group fed with antibiotics [ 21 ]. These results coincide with those demonstrated in the present study, where greater weights and lengths of the GIT of the birds of the PRE group were found, compared to the diet with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the supplementation with 0.2% mannanoligosaccharides (MOS) in a broiler significantly increased the weight of the duodenum, jejunum, and ileum at 42 days, while the group that was administered with oxytetracycline showed a decrease in weight in the jejunum. In the same study, the length of the duodenum increased significantly in chickens fed MOS, and a decrease in length was shown for the group fed with antibiotics [ 21 ]. These results coincide with those demonstrated in the present study, where greater weights and lengths of the GIT of the birds of the PRE group were found, compared to the diet with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The functionality of date pit powder as a food ingredient has been examined in its raw form, and in the form of microbially digested date pits, defatted date pits, or extracted protein (Al-Farsi and Lee, 2011;Akasha et al, 2016;Alyileili et al, 2020b). Date pits have been used in synthesis of a nanoparticle powder via hydrolysis with acid followed by ultrasound-assisted extraction, combined with the use of waterbased and methanol-based solvents.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Recently, there have been trends to utilize the phytochemical properties of industrial fruit or herbs wastes in animal feeding, which will not only reduce environmental burdens, but also improve animal production and health [ 47 , 48 ]. Similarly, phytochemical or nutraceutical prosperities of date pit or waste have been explored or attempts have been made to improve them using solid state degradation by Trichoderma reesei L. and their utilization in animal feeds [ 49 , 50 , 51 , 52 , 53 ]. Alyileili et al [ 49 ] reported that solid state degradation of date pit with T. reesei enhanced mannan oligosaccharide content, phenolic (142 g gallic equivalent/kg) and flavonoid (117 g rutin equivalent/kg) content of degraded date pits and antioxidant activities.…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%
“…Therefore, extra-nutritional effects of T. reesei -mediated solid state degraded date pit were explored in poultry [ 56 , 57 ]. The inclusion of 10% degraded date pits (phenolics, flavonoids and mannan–oligosaccharide) in the diets of broiler chickens increased catalase, superoxide dismutase and glutathione peroxidase activities in the serum, liver, and intestine, and decreased malondialdehyde content compared to the control group [ 50 ]. It also increased pancreatic enzyme activities, the villus length, and the villus/crypt ratio, and decreased the crypt depth of the intestine [ 51 ].…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%